(untitled) (The Pakistan Development Review, 1980)
This article has addressed itself to the delicate problem of evolving a development and employment strategy for a country still at its early stages of development and with traditional socio-economic structures. To modernise these structures and thus assist in achieving fuller and more productive employment, in reducing poverty and income inequality and in satisfying the basic needs of the mass of the population, the article based on the conclusions and recommendations of an ILO Mission has recommended a fourpronged attack: (1) a particular stress on rural development; (2) an urban strategy aiming at increasing the potential of the informal sector and at stimulating the rapid development of the industrial sector; (3) appropriate education, training and labour market policies; (4) finally, reforms in development planning and administration.